2008
DOI: 10.1152/japplphysiol.00021.2008
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle protein anabolic response to resistance exercise and essential amino acids is delayed with aging

Abstract: Skeletal muscle loss during aging leads to an increased risk of falls, fractures, and eventually loss of independence. Resistance exercise is a useful intervention to prevent sarcopenia; however, the muscle protein synthesis (MPS) response to resistance exercise is less in elderly compared with young subjects. On the other hand, essential amino acids (EAA) increase MPS equally in both young and old subjects when sufficient EAA is ingested. We hypothesized that EAA ingestion following a bout of resistance exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
323
8
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(364 citation statements)
references
References 60 publications
(83 reference statements)
28
323
8
5
Order By: Relevance
“…Among the amino acids, changes in leucine levels alone are sufficient to regulate the phosphorylation state and activity of the mTOR pathway (46,69). Several studies in rodents and human have shown that administration/ingestion of essential amino acids (specifically leucine) leads to increased/ enhanced protein synthesis in skeletal muscle primarily through activation of mTOR signaling (5,24,25,32,102). Currently, it is widely accepted that amino acid availability affects mTOR signaling and protein synthesis rate; however, how amino acids regulate the mTOR signaling pathway remains poorly understood.…”
Section: Mtor and Amino Acid Availabilitymentioning
confidence: 99%
“…Among the amino acids, changes in leucine levels alone are sufficient to regulate the phosphorylation state and activity of the mTOR pathway (46,69). Several studies in rodents and human have shown that administration/ingestion of essential amino acids (specifically leucine) leads to increased/ enhanced protein synthesis in skeletal muscle primarily through activation of mTOR signaling (5,24,25,32,102). Currently, it is widely accepted that amino acid availability affects mTOR signaling and protein synthesis rate; however, how amino acids regulate the mTOR signaling pathway remains poorly understood.…”
Section: Mtor and Amino Acid Availabilitymentioning
confidence: 99%
“…These volunteers were studied previously and therefore the subject characteristics can be found elsewhere (23). The subjects were not engaged in any regular exercise training at the time of the enrollment, however, they were physically independent and overall healthy.…”
Section: Subjectsmentioning
confidence: 99%
“…This was immediately followed with the ingestion of 20 g of a leucine-enriched essential amino acid mixture. The composition of the essential amino acid mixture was published previously (23). Subsequent muscle biopsies were sampled at 3 and 6 h postexercise.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations